Developing A Supplementary Reading Text Based on Nias Local Culture - Mega Kristin Zebua; Yenita Br Sembiring; Carolin Mutiara Pakaphan (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The aim of this research is to develop supplementary English Book for grade eight at SMP Markus Medan. This research is classified into Research and Development (R&D) study. The participants of this research were the students from grade eight of Markus Medan, English teacher, and lecturers from English Department. The writer gathered the data from questionnaires given to the participants. The first questionnaires were given to the students to find their suitable needs and characteristics in learning English. The second questionnaires were administered in validating the first draft of supplementary English book that developed by the writer. The third questionnaires were given to get the feedback from the students on the second draft of supplementary English book. The final product of this research was passed by having a series of material design steps, namely: collecting preliminary information, writing tasks grids, designing the first draft of supplementary English book., validating the developed draft of supplementary English book, revising the draft of supplementary English book, conducting tryouts, evaluating, and revising the final draft of supplementary English book. The writer developed the tasks into four units that cover nine reading skills. It can be known form the result from the third questionnaires which shows the mean of each aspect of the tasks ranging from 3.6 to 5.0. Therefore, it can be concluded that the supplementary English book is appropriate for students from grade eight of SMP Markus Medan.